The Instructor's Guide for Promoting Presenter Empowerment Actions and Evaluating Presenters During Patient− and Family-Centered Rounds - Sarah Vepraskas; Michael Weisgerber; Heather Toth; Dawn Bragg (Association of American Medical Colleges, 2015)
Abstract Introduction Medical students and interns are essential communicators during patient− and family-centered rounds. While specific behaviors of excellent senior residents, attendings, and nurses have been identified, behaviors that make medical students and interns excellent presenters has not been previously studied or identified. This resource introduces two tools designed to help train learners to be excellent presenters: (1) a behavior checklist for training observation and immediate feedback, and (2) a card template with presenter empowerment actions (PEAs) that can easily be used by presenters. Methods The behavior checklist, the PEA-21 (a 21-item PEA checklist), was created after we conducted a literature review, structured interviews, and observed rounds, followed by iterative discussion among study team members. The PEA-21 incorporates our results, which are organized into a spot-on, style, synthesize, and sleuth (4S) framework, consistent with previous card templates for senior residents and attendings (e.g., Rounding Like a Ninja and the 4S Format). A rounding card was then created for presenters, with the PEAs organized in the same 4S framework as the observational checklist. The behavior checklist and the card template provide an evidence-based approach to evaluating and promoting the use of PEAs. Results After 22 pediatric interns attended a workshop that both introduced and taught them how to use PEAs, they reported learning basic knowledge on empowerment, increased confidence, and the intent to incorporate PEAs into their rounding practice. There is overlap between PEAs and selected areas within the ACGME Pediatric Milestones. As a result, educators can use the PEA-21 to provide their learners with targeted feedback both to enhance their presentation skills and for milestone evaluation. Discussion The two tools in this publication were well-received by learners and presenters. We recommend clinical educators use the PEA-21 for the development and improvement of early learners' (i.e., students and interns) presentation skills.